Electromagnetic field dosimetry - Gajšek, Peter (Zdravstveno varstvo, 2004)
In the last three decades, the use of devices that emit electromagnetic fields(EMF) has increased dramatically. The proliferation of EMF devices has been accompanied by concern about ensuring the safety of their use. An important segment of the EMF research that looks after the biological effects of EMF is dosimetry which correlates external electric fields with those within tissues. Better methods are needed to properly measure, extrapolate orrelate effects observed in animals to those expected to be found in people. The resulting data could lead to modification of existing safety standards or setting of new safety standards. Accurate dosimetry represents an essential element of the research in determining the biological effects of electromagnetic fields. In the present paper, an overview over currently usedexperimental and numerical dosimetry methods in bioelectromagnetics research are given.
Keywords: biološki sistemi; Dosimetry; dozimetrija; Electromagnetic fields; elektromagnetno sevanje; meritve; metode; negativni vplivi; škodljivost